Eisosomes promote the ability of Sur7 to regulate plasma membrane organization in Candida albicans - Wang, Hong X. (Mol Biol Cell, 2016)
The plasma membrane of the fungal pathogen Candida albicans forms a protective barrier that also mediates many processes needed for virulence, including cell wall synthesis, invasive hyphal morphogenesis, and nutrient uptake. Because compartmentalization of the plasma membrane is believed to coordinate these diverse activities, we examined plasma membrane microdomains termed eisosomes or membrane compartment of Can1 (MCC), which correspond to ∼200-nm-long furrows in the plasma membrane. A pil1∆ lsp1∆ mutant failed to form eisosomes and displayed strong defects in plasma membrane organization and morphogenesis, including extensive cell wall invaginations. Mutation of eisosome proteins Slm2, Pkh2, and Pkh3 did not cause similar cell wall defects, although pkh2∆ cells formed chains of furrows and pkh3∆ cells formed wider furrows, identifying novel roles for the Pkh protein kinases in regulating furrows. In contrast, the sur7∆ mutant formed cell wall invaginations similar to those for the pil1∆ lsp1∆ mutant even though it could form eisosomes and furrows. A PH-domain probe revealed that the regulatory lipid phosphatidylinositol 4,5-bisphosphate was enriched at sites of cell wall invaginations in both the sur7∆ and pil1∆ lsp1∆ cells, indicating that this contributes to the defects. The sur7∆ and pil1∆ lsp1∆ mutants displayed differential susceptibility to various types of stress, indicating that they affect overlapping but distinct functions. In support of this, many mutant phenotypes of the pil1∆ lsp1∆ cells were rescued by overexpressing SUR7. These results demonstrate that C. albicans eisosomes promote the ability of Sur7 to regulate plasma membrane organization.